Efforts to Improve Students' Motivation to Learn Arabic Language Through the Implementation of the Reward and Punishment System in Grade VII of MTsN 2 Bandung City - Futri Fauzia Alawia; Agus Karim; Ade Arip Ardiansyah (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to explore the effectiveness of the implementation of reward and punishment system in increasing the motivation to learn Arabic language of seventh grade students at MTsN 2 Bandung. The research method used is an experiment with a pre-test and post-test control group design. The research participants consisted of two groups, namely the experimental group that would apply the reward and punishment system, and the control group that did not apply the system. The results of this study show that the implementation of reward and punishment system has a significant impact on students' learning motivation. The experimental group showed a significant increase in Arabic learning motivation compared to the control group. In addition, observations of students' participation, concentration level, and level of interest in Arabic lessons also showed a significant increase in the experimental group. The findings of this study indicate that the use of reward and punishment system can be an effective strategy in increasing students' motivation to learn Arabic in class VII H at MTsN 2 Bandung. The implication of this study is the importance of considering the application of motivational strategies based on reward and punishment as part of efforts to improve the quality of Arabic language learning in secondary schools.